(3EUdGM GdefWbs - (3jYbhH Hf ESMGb, CHh jhSa, GHf GdScjJ,J (B224 (3g` s
(3ChdgG (B:s
(3jHOC HHGH narYd hparYd HGNJdGa GdeYfi s
(3BNQgG (B:s
(3jfJgi HHGH eG dG jJcde Hg EdG HGdLMO s
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B195 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B243 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B2 - (3U (B536s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B108s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI ehdGfG YHO GdYRjR GdMejfi s
Keywords: (3GddZIs